The Implementation of National Health Insurance Policy At Puri Medika Tanjung Priok Hospital, Jakarta Indonesia - Elfrida Novita Savitri; Sondang Dormaida Silaban; Karolina Baransano; Erlina Puspitaloka Mahadewi (CV. Inara, 2025)
The present study reports the comprehensive study on BPJS health recently, as a form of change from PT. Askes in Indonesia, which previously became the organizer of health insurance for all Indonesian people. The JKN program organized by BPJS health aims to improve the social welfare of the community by providing convenience in public services, especially in the health sector. This study aims to examine how the implementation of the national health insurance policy and what are the obstacles in implementing the National Health Insurance policy through the Health Social Security Administering Agency (BPJS) at Puri Medika Hospital, Tanjung Priok, Jakarta, Indonesia. The researcher used a descriptive qualitative research method. The data used in the study were primary and secondary data. Data collection used interview, documentation and observation techniques. The data were analyzed using the Milles and Huberman data analysis model and presented in the form of a TOWS analysis diagram. The implementation of National Health Insurance at Puri Medika Hospital, Tanjung Priok, Jakarta, Indonesia is in the good category. The inhibiting factors for implementation are the limited number of registration officers, lack of public knowledge, and waiting times for health services that still need to be improved.